CONTROL OF THE DIGITAL MODEL IN PUBLIC PROCUREMENT PROCEDURES - Szőke, Brigitta; Cuprik, Vanda (Acta Carolus Robertus, 2021)
In our study, digital models used in public procurement procedures are interpreted through various examples. As it is not possible to know what bids are being received from market participants during the preparation of the procedure, and linear thinking is not valid, a wide-ranging impact assessment of the digital model should be carried out during the preparation and the evaluation method should be carefully defined not only for suitability. the value of the quality parameter, but also the value below which the contracting authority considers the more favorable tender content element only with this value. As with all modeling, it is important that inputs suitable for analysis are provided and conclusions are drawn with these (as well as the properties of the model) in mind. If there is no general legality, the conclusions should state their validity - to avoid misunderstandings. You should also be aware that it is not possible to know what bids will be received during the preparation of procurement procedures. The model also works for extreme input data, but the usability of its results is questionable. In fact, experience is gained in all public procurement procedures that can be used in the next procedure with a similar subject.
Keywords: public procurement; digital model; point allocation method; quality sub-aspect